Development and Validation of a Stability-Indicating High-Performance Liquid Chromatographic Method for the Quantification of Methocarbamol and Its Impurities in Pharmaceutical Dosage Forms. (5th January 2021) - Kalokhe, Shivani; Nalwade, Santaji; Patil, Pallavi; Raskar, Poonam
Abstract: A novel, delicate, stability-indicating, gradient, reversed-phase high-performance liquid chromatographic method has been established for the quantitative estimation of methocarbamol (MTC) and its impurities present in a pharmaceutical oral suspension. XBridge C18, 5 μm, 250 mm × 4.6 mm column was used to accomplish chromatographic separation with a buffered mobile phase consisting of a mixture of 0.01 M of sodium dihydrogen phosphate (pH 7.0 buffer) and methanol in the ratio of 95:05 (v/v), respectively, were used as solvent A and a mixture of methanol and Milli-Q water in the ratio 90:10 (v/v), respectively, was used as solvent B. Analysis was carried out at 0.8 mL/min flow rate and the detection wavelength at 225 nm. The compartment temperature of the column is put at 25°C. The resolution of MTC and its four impurities has been attained >2.0 for all pairs of compounds. Significant degradation of MTC was photolytic, thermal and oxidative stress conditions. Validation of the developed method was performed as stated by the International Conference on Harmonization guidelines with regard to all validation parameters like specificity, accuracy, linearity, precision, limit of detection, limit of quantitation and robustness.